Review: the potential impact of surface crystalline states of titanium for biomedical applications. (3rd April 2018) - Barthes, Julien; Ciftci, Sait; Ponzio, Florian; Knopf-Marques, Helena; Pelyhe, Liza; Gudima, Alexandru; Kientzl, Imre; Bognár, Eszter; Weszl, Miklós; Kzhyshkowska, Julia; Vrana, Nihal Engin
Abstract: In many biomedical applications, titanium forms an interface with tissues, which is crucial to ensure its long-term stability and safety. In order to exert control over this process, titanium implants have been treated with various methods that induce physicochemical changes at nano and microscales. In the past 20 years, most of the studies have been conducted to see the effect of topographical and physicochemical changes of titanium surface after surface treatments on cells behavior and bacteria adhesion. In this review, we will first briefly present some of these surface treatments either chemical or physical and we explain the biological responses to titanium with a specific focus on adverse immune reactions. More recently, a new trend has emerged in titanium surface science with a focus on the crystalline phase of titanium dioxide and the associated biological responses. In these recent studies, rutile and anatase are the major two polymorphs used for biomedical applications. In the second part of this review, we consider this emerging topic of the control of the crystalline phase of titanium and discuss its potential biological impacts. More in-depth analysis of treatment-related surface crystalline changes can significantly improve the control over titanium/host tissue interface and can result in considerable decreases in implant-related complications, which is currently a big burden on the healthcare system.